The fate of Chinese refugees in post-war Indonesia, 1946–1947 - Alamsyah, Adi (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2024)
This article discusses the daily lives of the Chinese community in Indonesia after the proclamation of independence. Chinese community had a very different life compared to when Indonesia was still under Dutch colonial rule. Especially when the indigenous community (Bumiputra) voiced the adage "Siap Sedia" (Be Prepared) to ignite the spirit of Indonesian youth as motivation to defend Indonesian independence, so that Chinese community had to evacuate to secure and save themselves from the consequences of the conflict between the Republic of Indonesia and Dutch forces. This article aims to understand the conditions and daily lives of the Chinese community, considered as part of the colonial legacy. The article uses historical research methods including heuristic, verification, interpretation, and historiography. The article generates an understanding that there is a fluctuating dynamic in the lives of the Chinese community, especially in relation to the indigenous community.